Addressing Bias and Stigma in the Language We Use With Persons With Opioid Use Disorder: A Narrative Review. (January 2022) - Werder, Karen; Curtis, Alexa; Reynolds, Stephanie; Satterfield, Jason
BACKGROUND: Despite an increase in access to medications for opioid use disorder, less than 20% of individuals with opioid use disorder (OUD) receive treatment. Stigmatizing language has been identified as a potential trigger for explicit and implicit biases that may adversely affect treatment enrollment and quality of care for persons with OUD.AIMS: To conduct a narrative review of the literature on stigmatizing language and OUD, examine how treatment outcomes are affected, and present strategies to reduce bias and promote OUD treatment.METHOD: A narrative review of the literature between 2010 and 2019 was conducted using CINAHL, PubMed, and PsycINFO. Key search terms were opioid use disorder (or substance use disorder ), stigma, and language . Fifty-two articles were screened for inclusion, and 17 articles were included in this review.RESULTS: The articles reviewed provide consensus that stigmatizing language toward persons with OUD fosters explicit and implicit bias and impedes engagement in treatment. Four themes emerged: (1) stigma and language, (2) stigma and language used by health care professionals, (3) stigma and language used by the general public, and (4) stigma and language used by people with OUD.CONCLUSIONS: Stigmatizing language is dehumanizing and plays a pivotal role in bias and discrimination that may contribute to unsatisfactory treatment outcomes among persons with OUD. Health care professionals, nursing in particular, must assume an intentional stance against stigma perpetuated toward persons with OUD through advocacy in education, practice, policy, and the media.